Evaluación de la eficacia de una vacuna antirrábica cepa "Flury" Lep en bovinos - GonzáIez G., Guillermo; Barrera, Carmenza (Instituto Colombiano Agropecuario, 2019)
The Habel test for potency and the inmune response of cattle vaccinated with a product prepared with a Low passage Flury strain of rabies inactivated with B-propiolactone and with addition of adyuvant was measured. The Habel test gave protection to 63.000 Mouse Lethal Dose 50. However, some inmune responses were observed only until 9 months after vaccination when only 30% of the vaccinated cattle developed neutralizing antibodies. None of the vaccinated cows showed neutralizing titers equal or higher than 1:2 against 100 MLD50 , twelve months after vaccination.